Pengaruh Laba Kotor, Laba Operasi Dan Laba Bersih Terhadap Prediksi Arus Kas Di Masa Mendatang Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Umi Mas’ulah; Iip Dyah Kusumaningati; Sarmila Sarmila (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to determine the effect of gross profit, operating profit and net income on predicting future cash flow in consumer goods industry companies listed on the Indonesian Stock Exchange in 2018-2022. This research method uses a quantitative research approach with experimental research types. The samples this study were 23 companies with the sampling technique using purposive sampling method so that. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that gross profit has a significant effect on predicting future cash flow whit a t-count value of 17,769 > t-table of 1,980 and a significant value of 0,000 < 0,05. Operating profit has a negative and significant effect on predicting future cash flow with a t-count value of -7,116 > t- table of 1,980 and a significant value of 0,000 < 0,05. Net income has a significant effect on predicting future cash flow with a t-count value of 3,488 > t- table of 1,980 and a significant value of 0,001 < 0,05. While the result of the study simultaneous gross profit, operating profit and net income have a significant effect on predicting future cash flow with a f-count value of 673,251 > f-table of 3,08 and a significant value of 0,000 < 0,05.